Enhancement of fault analysis method using ARC resistance formula - Omidi, Houman (2013)
Generally there are two different methods in calculation short-circuit currents in power system networks in terms of considering arc resistance in calculations, first method is based on considering the value of the arc resistance as a constant value (usually 0.5O) or neglecting this value. By introducing some formulae for the arc resistance like the Warrington formula which is one of the most well-known formulae second method could be applied. Second method is based on considering the value of the arc resistance in short-circuit calculation. To calculate the short-circuit current in power system networks our model should be accurate enough, to have an accurate model in theses studies the value of the arc resistance should be considered. The problem here is the non-linear relationship between fault current and arc resistance. By using more accurate formula like Terzija has been proposed in one of the recent studies values of short-circuit current and arc resistance can be identified more accurate but still there are some problems relates to the high fault currents. In this study by using ETAP software for fault analysis, Microsoft visual studio 2010 (C++ programming) for the related iteration and one the most recent formula for the arc resistance, short-circuit studies based on symmetrical components has been investigated on two different IEEE networks; IEEE 30-bus and IEEE 34-bus test feeders. Results have been compared with fault analysis based on phase coordination in the same network and shows the efficiency of the arc resistance formula which has been used in this study in special range of fault currents in balanced and unbalanced networks.